Peran Guru PAI dalam Meningkatkan Akhlak Siswa di SMP Dharma Utama Desa Sukasari - Muhammad Dirar Nst; Robie Fanreza; Syahril Zendrato; Ilham Soleh silitonga (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Each person has a different character, especially within the scope of the school, all students have different behavior and characteristics, so a Pai teacher plays a very important role in improving the honorable morals of each student at Dharma Utama Middle School, Sukasari village. In improving the quality of students' morals towards anyone, a PAI teacher educates and instills nobility by using interesting learning methods so that students do not get bored and fed up. A pai teacher most importantly instills the qualities of honesty, patience in students in studying, and in learning the pai teacher is also required to understand various learning methods so that students are active, responsible and disciplined. Slowly, lazy students will think, their hearts will be touched if the method applied is appropriate and relevant for every student at Dharma Utama Middle School. The first method used is a direct learning strategy and the second is cooperative learning (creating groups in learning).